SISTEM PENGAMBILAN KEPUTUSAN MULTI KRITERIA PADA INDUSTRI JASA UNTUK MENINGKATKAN DAYA SAING USAHA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN MENGGUNAKAN MINIMUM DEVIATION METHOD (Studi Kasus Di CV. Transpatindo, Berbah, Sleman, DIY) - Gunawan Madyono Putro (Jurusan Teknik Informatika, 2016)
CV. Transpatindo is a company engaged in the delivery of goods. To improve the competitiveness of enterprises in the era of the Asean Economic Community, which opened in 2016, then the company needs to improve customer satisfaction in order to service customers more loyal CV. Transpatindo. To improve customer satisfaction will certainly increase operating costs, so as not to decrease the competitiveness of enterprises it is necessary to minimizing operational costs. This study aims to maximize customer satisfaction with each mempertimbangka to minimize the cost operasional.Upaya to maximize customer satisfaction with still consider to minimize the operational cost is the problem of multi-criteria decision making, because maximizing customer satisfaction and minimize production costs are two conflicting objective functions ( contradictory). To find a compromise solution between the two functions of these objectives will be done using the minimum deviation method. Steps to resolve the problem using the minimum deviation method is to determine the ideal solution each objective function, create tables payoffnya, create a mathematical model of permasalahn solved using the minimum deviation method, completed the mathematical model to obtain a compromise solution of two conflicting objective functions. A compromise solution that is obtained is the value of customer satisfaction is 4.9 which is ideally a value of 6. Operating cost per day is US 2.116 million, - where the value of the ideal is Rp 1.250.000, -. Weight of packets sent per day are shipped per day A package weighing 100 kg